Gastric heterotopia together with squamous metaplasia in the gallbladder - Mariana S Daud (Acta Gastroenterológica Latinoamericana, 2007)
Heterotopic gastric mucosa in the gallbladder is extremely unusual. In this study, we aimed to report a case of gastric heterotopia together with squamous metaplasia in the gallbladder of a 47-year-old female patient who experienced an intensive abdominal pain. He was admitted to the hospital for clinical treatment without any improvement. Ultrasonography showed a stone located in the gallbladder neck and dilatation of intrahepatic bile ducts, both hepatic ducts and common hepatic duct. Laparoscopic cholecystectomy was performed. In the microscopical examination, the epithelium of the gallbladder revealed an unspecified chronic cholecystitis. Besides, at the level of the gallbladder body, a heterotopic gastric mucosa contain chief, parietal and mucosal cells with cystic glands and squamous metaplasia was found. Actually the patient is in long-time follow-up, asymptomatic. We also review 96 other reports of HGM in the gallbladder in the international medical literature from 1934. As heterotopic tissue may promote carcinogenesis of the gallbladder, close attention should be paid to any occurrenceof such lesions in this anatomical region. It appears that laparoscopic cholecystectomy may be unavoidable for patients affected by heterotopic gastric mucosa at the present time and care must be taken when a diagnosis is made based on intraoperative frozen sections.